Sectoral Innovation Systems, Corporate Strategies, and Competitiveness of the German Economy in a Globalised World - Michael Rothgang (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
The EU Barcelona target assumes a close causal relationship between corporate R&D, the competitiveness of business firms and the economic performance of industrial countries. Testing this hypothesis, this paper contrasts innovation and production activities in four research-intensive manufacturing sectors (chemicals and pharmaceuticals, motor vehicles, machinery, and electrical engineering). Starting point are observed long-term changes in world- wide value added of the manufacturing sector. The empirical analysis is based on a unique survey of R&D-intensive business firms in Germany and 50 personal interviews in large industrial companies. The results show that there is no simple connection between R&D and competitiveness. Moreover, the likely consequences of promoting R&D differ substantially between industries.
Keywords: L6; O23; R32; 330; Sectoral innovation systems; corporate R&D Strategies; chemicals and pharmaceuticals; machinery; electrical engineering; motor vehicles; bazaar effect; Verarbeitendes Gewerbe; Betriebliche Forschung; Innovationsmanagement; Internationaler Wettbewerb; Europäische Forschungs- und Technologiepolitik; Deutschland